Mentalizacja z perspektywy rozwojowej i klinicznej - Redakcja (Wydawnictwo Naukowe UAM, 2016)
This work presents theoretical analyses and empirical research aimed at showing the capability for mentalization from the developmental perspective. Two aspects are taken into consideration: the importance of models of attachment shaped by the child’s early relations with the mother for appropriate development, and the clinical perspective. The latter concentrates not only on describing is capability in different psychological disorders, especially schizophrenia and borderline personality disorders, but also on explaining the inﬂuence of various social contexts on activating intrapsychic representations impacting on reduced ability to mentalize. The book is addressed to students of psychology, cognitive science, education and psychiatry, as well as to researchers not afraid of formulating new research questions and taking up new challenges in the various disciplines seeking to explain human behaviour.

W psychologii klinicznej mentalizacja stała się ważnym konstruktem teoretycznym, który znajduje szerokie zastosowanie w wyjaśnianiu uwarunkowań i mechanizmów kształtowania się zdrowia i różnych zaburzeń psychicznych. Autorzy niniejszego opracowania prezentują problematykę mentalizacji w wielu różnych kontekstach teoretycznych i empirycznych. Szczególną uwagę poświęcają ujęciom: psychoanalizie i podejściu psychodynamicznemu, paradygmatowi poznawczemu i integracyjnemu oraz współczesnej neuropsychologii. Przybliżają metody badania mentalizacji emocjonalnej i teorii umysłu, a także prezentują wyniki badań własnych w tym obszarze. Książka jest skierowana do studentów psychologii, kognitywistyki, pedagogiki i psychiatrii, osób profesjonalnie zajmujących się pomaganiem i psychoterapią, a także naukowców, którzy nie obawiają się weryfikowania już znanych i formułowania nowych pytań badawczych oraz podjęcia wyzwań w obszarze różnych dyscyplin wyjaśniających zachowanie człowieka.
Mentalization from the developmental and clinical perspective
Keywords: zaburzenia osobowości; mentalizacja; przywiązanie